Viagem ao mundo das águas: criação de cartilha como apoio para visita em estação de tratamento de água - Rodrigues, Lenita Gomes de Oliveira (Universidade Federal de São Carlos, 2023)
The objective of this work is to explore the knowledge of the water cycle in nature, its importance and the basics of sanitation through teaching about ecology and society as an educational process. The aim is to help students gain a better understanding of nature, water, and the environment in which they live, contributing to the formation of responsible citizens. This work argues that an eco-educated community is one in which people organize around issues related to quality of life and the environment and that it is the responsibility of governments to provide solutions to ensure access to water, health, and dignity for all. The creation of a free, accessible, and assertive e-book is proposed that teachers can use to educate students about the water cycle, its use, and the ecological aspects of society's responsibility for the environment. The material is justified by the need to contextualize the relationship between ecology, education and society and to provide teachers with a resource that they can use to support environmental education.
Journey to the world of water: creation of a booklet for school visits to water treatment plants
Keywords: Ecologia; Saneamento; Meio ambiente; Basic sanitation; Ecology; Environment; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO